Space-time spectrum sharing based on game theory:dynamic access and penalty strategy - Yangyang NIU; Zhiqing WEI; Zhiyong FENG (Tongxin xuebao)
To tackle the challenge of inefficient utilization of spatiotemporal spectrum resources in heterogeneous networks, a reliable spectrum sharing strategy based on game theory was proposed for scenarios where multiple secondary users dynamically access through sensing spatiotemporal spectrum opportunities.Firstly, secondary users sensed the activity state of primary users through channel sampling and subsequently seek suitable spatiotemporal spectrum opportunities.Each secondary user aimed to access more spectrum resources while preventing quality degradation between primary users.Consequently, a negotiation of individual utilities between secondary and primary users was needed, in order to reach a mixed Nash equilibrium.When the secondary user's transmission power was abnormal, its behavior would be regarded as a violation.Then, a backoff time compensation algorithm was presented to penalize the secondary users, according to the number of violations and active nodes in the network.Finally, simulation results validate the effectiveness of the spatiotemporal spectrum opportunities sharing strategy with the penalty mechanism.